Modal Coupling Coefficients and Frequency/Bias Planes for Gyromagnetic Boundary Value Problems - Junaid Zafar; Tasneem Zafar; Haroon Zafar (Institute of Advanced Engineering and Science, 2012)
In this paper, electromagnetic and uniform precession magnetostatic mode interaction theory is reformulated to include comprehensive electromagnetic modal impact in the determination of modal coupling calculations. For this purpose orthogonal electromagnetic and normal magnetostatic modes character is solved with coupled field Maxwell’s equations and vectorized magnetization expression to model the interactions between electromagnetic modes and magnetostatic uniform precession mode. Calculations for modal coupling factors are presented here for the first time and frequency/ bias planes are constructed using the developed modal interaction formulation with an ameliorated accuracy. The proposed formulation is validated and tested against closed form frequency/ bias solutions concerning these gyromagnetic boundary value problems.DOI:http://dx.doi.org/10.11591/ijece.v2i5.222